An exploratory study on the collection development efforts of the Ateneo de Manila High School Educational Media Center in adherence to the Enhanced Basic Education Act of 2013 and its prescribed senior high school tracks - Ishihara, Rio Anne A.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
The Philippine Legislature has enacted the Republic Act 10533 or Enhanced Basic Education Act of 2013 as a thrust to strengthen the education system in the country. The main consideration of said Republic Act is to add two (2) more years in basic education, with uniform adjustments on government, public, and private education sectors through adopting a prescribed curriculum.

This study zoned in on the consequential effects of the legislation upon the library, particularly in the Ateneo de Manila Educational Media Center, focusing mainly on the responses, adjustments, and considerations of its librarians as regards the implementation of the prescribed curriculum. Interviews with the professional librarians, tabulations for the current and previous library resources, as well as the prescribed curriculum were examined alongside each other as inferences were gleaned from established methods of analysis. Such analysis revealed that albeit the pre-existing resources and competent manpower, issues such as time constraint, logistical considerations and the limitations brought by the establishment of a new and untested curriculum need to be properly addressed.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Republic Act 10533.; RA 10533.; Enhanced Basic Education Act of 2013.; Ateneo de Manila High School Educational Media Center